Analisis Pengaruh Motivasi, Persepsi dan Sikap Konsumen terhadap Keputusan Pembelian - Achmad Fajaruddin (Islamic Economics Journal, 2016)
With the advance of technology and the civilization, the more advanced needs of consumers as well. Consumers are increasingly critical. Especially women in relation to beauty products. Thus research is needed to find out more about the factors that influence purchase decisions. This study aimed to analyze the factors that influence purchasing decisions Wardah beauty products at the student campus Unida Mantingan 2014-2015, as well as find out what factors most influence on purchase decisions Wardah products. This research is quantitative descriptive. To achieve the desired aim, the authors tried to collect primary data by distributing questionnaires to 80 respondents using simple random sampling. Once collected, the data will be analyzed using content analysis method, the classical assumption test, multiple linear regression, R-square, Ftest and t-test. Results from the analysis conducted on the validity and reliability, there is one question that is not valid, namely the consumer attitude variables with production indicators Wardah products. Results of the analysis showed the influence of independent variables on the dependent variable is less influential, it can be concluded that the influence of motivation, perceptions and attitudes of consumers on product purchasing decisions Wardah by 28%, while the remaining 72% is determined by other variables outside the study.